Related diversification using core competencies in South Korean dairy industry - Dawon Kim; Rosa Kim; Tongwon Lee; Seungho Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This study aims to examine how unrelated diversification facilitate firm's growth and innovation. To achieve this goal, we investigate how Maeil Dairies has diversified through open innovation as the Korean dairy market struggles to maintain its size. Maeil Dairies, one of the top three conglomerates in the Korean dairy industry, has gone through different forms of diversification both related and unrelated to its core competencies. This study presents what the overlapping competencies are in its diversified products and businesses, analyzes the effectiveness of diversification in terms of relatedness, and examines the need for unrelated diversification. By analyzing the four diversification categories of the Maeil Dairies case and applying diversification theory, this study shows that although related diversification is more recommendable in most circumstances, unrelated diversification may present new opportunities and is necessary in order to avoid stagnation and falling behind.
Keywords: 650; case study; core competencies; Korean dairies market study; open innovation; related diversification; unrelated diversification